2009
DOI: 10.1103/physrevlett.102.256601
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Coupling between Current and Domain Wall Motion in (Ga,Mn)As

Abstract: We consider current-induced domain wall motion and, the reciprocal process, moving domain wall-induced current. The associated Onsager coefficients are expressed in terms of scattering matrices. Uncommonly, in (Ga,Mn)As, the effective Gilbert damping coefficient alphaw and the effective out-of-plane spin-transfer torque parameter betaw are dominated by spin-orbit interaction in combination with scattering off the domain wall, and not scattering off extrinsic impurities. Numerical calculations give alphaw appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 28 publications
1
64
0
Order By: Relevance
“…31,32 Nearly a century ago it was discovered that in macroscopic bodies the magnetization of a ferromagnet couples to the mechanical degree of freedom: Barnett demonstrated that a mechanical rotation of a demagnetized ferromagnet creates a net magnetization along the rotation axis, 33 whereas Einstein and de Haas showed that reversing the magnetic moment of a ferromagnetic cylinder induces a mechanical torque. 34 Both effects are governed by the same gyromagnetic tensor.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Nearly a century ago it was discovered that in macroscopic bodies the magnetization of a ferromagnet couples to the mechanical degree of freedom: Barnett demonstrated that a mechanical rotation of a demagnetized ferromagnet creates a net magnetization along the rotation axis, 33 whereas Einstein and de Haas showed that reversing the magnetic moment of a ferromagnetic cylinder induces a mechanical torque. 34 Both effects are governed by the same gyromagnetic tensor.…”
Section: Introductionmentioning
confidence: 99%
“…In metals it also covers the appearance of a DW resistance at abrupt interfaces [55][56][57][58], leading to a momentum transfer force [7,[59][60][61][62] never clearly identified experimentally [63]. Two contributions have been identified in the spin-relaxation nonadiabatic torque.…”
Section: B Spin-transfer-like Torquesmentioning
confidence: 94%
“…Therefore, the determination of the effective magnetic field and the parameters in the LLG equation, such as α and β, is an important issue for magnetization dynamics study. 12,14,15,20,21 Previously, we have derived the Gilbert damping (α) term based on the kinetic spin Bloch equation (KSBE) approach 22 in homogeneous ferromagnetic systems. 21 In the present work, we derive the whole LLG equation from the s-d model in inhomogeneous ferromagnetic systems based on the same approach.…”
Section: Introductionmentioning
confidence: 99%
“…20), and m = 0.5m e with m e representing the free electron mass, one estimates the spin stiffness A ss ∼ 1 pJ/m in GaMnAs. 26 However, the other effective field in the form −…”
mentioning
confidence: 99%